LEGAL PROTECTION FOR LOCAL PRODUCTS THE SPIRIT OF SOBEAN AS A CITY BRANDING IN THE CONTEXT OF TOURISM MARKETING - I Wayan Landrawan; Ni Ketut Sari Adnyani; Dewa Ayu Eka Agustini (Jurnal Komunikasi Hukum, 2023)
This study aims to determine, among others: (1) the formulation of indigenous village participation policies in the development of City Branding The Spirit of Sobean as a tourism marketing strategy in Buleleng Regency; (2) implementation of the policy formulation of traditional village participation in the development of City Branding The Spirit of Sobean as a tourism marketing strategy in Buleleng Regency; and (3) the implications of implementing the policy formulation of traditional village participation in the development of City Branding The Spirit of Sobean as a tourism marketing strategy in Buleleng Regency. This research is a normative juridical research with a statutory approach and a conceptual approach, the determination of the location and the research sample is determined purposively. Data collection techniques by means of observation, interviews and document studies. The research data analysis technique used descriptive qualitative analysis techniques. The results showed that the potential of the Buleleng area with the branding of The Spirit of Sobean. The development of the city branding of The Spirit of Sobean, Buleleng Regency with all existing components or sub-systems from local governments, entrepreneurs, and the arts and culture community can carry out the highest level of engaging tourism. The implication of the application of legal protection in the development of city branding The Spirit of Sobean is very large as a driver of sustainable tourism.